An Ensemble Deep Learning Technique for Plant Identification - Prasad, P. Siva; Senthilrajan, A (International Journal of Computer Sciences and Engineering, 2020)
Plant identification system is helped to find unidentified plants. Plant identification is most difficult task with the existing classification algorithms. Many existing classifiers are present to identify the plant species with the help of leafs. With the various drawbacks, the system will not reach that much. In recent years, many applications belong to various domains and technologies are using the Deep Learning (DL) for rapid and better results. In this paper, the Novel Approach (NA) is introduced with the combination of CNN adopted with ensemble methods such as bagging and boosting. This paper addresses that the Convolutional Neural Network (CNN) with ensemble methods is better than Machine Learning methods to identify the plant by leaf. The ensemble methods are to improve the accuracy and sensitivity of plant identification model. The parameters such as sensitivity and accuracy are the two metrics to show the performance.